2010
DOI: 10.1111/j.1463-1318.2009.01988.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of patient‐controlled sedation for colonoscopy: Entonox vs modified patient‐maintained target‐controlled propofol

Abstract: Both Entonox and the modified TCI propofol provide equally effective sedation and pain relief, simultaneously allowing patients to be easily manoeuvred during the procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…TCI is easy to use and provides a high level of confidence regarding the predictability of anesthetic effects. Relatively few studies have evaluated the use of TCI for sedation during GI endoscopy (13,14). In our study, we used TCI to administer propofol and alfentanil during endoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…TCI is easy to use and provides a high level of confidence regarding the predictability of anesthetic effects. Relatively few studies have evaluated the use of TCI for sedation during GI endoscopy (13,14). In our study, we used TCI to administer propofol and alfentanil during endoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In a study comparing administration of continuous 50% nitrous oxide and patient-maintained, target-controlled propofol, Maslekar et al 26 found similar patient satisfaction and analgesic and sedative effects in the two groups. Propofol is a short-acting hypnotic agent, which is increasingly being used during colonoscopy.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, patient-maintained sedation (1999) [45] is sedation according to a set estimated target concentration of the drug (target controlled infusion [TCI]) where the patient can adjust the system to increase the steady state concentration of the drug. The two techniques have also been combined (2011) using TCI for baseline sedation and PCS for additional doses of propofol according to the patient's extra demand of anxiolytics [46]. For the past decades, evaluation of PCS has focused on these early identified areas, the patients' preference for different techniques to diminish stress, and finding a suitable system for a variety of procedures.…”
Section: Patient-controlled Sedation (Pcs)mentioning
confidence: 99%
“…Procedure-related quality has usually been evaluated in terms of efficiency or time periods in comparison to a standard sedation regimen. In most cases, PCS has been evaluated as at least equal to the standard: number of oocytes retrieved for in vitro fertilization [54], differences in procedure time and difficulty of performance [53], and surgeons' satisfaction [46].…”
Section: Outcome Measurementmentioning
confidence: 99%